Bisecting GlcNAc modification diminishes the pro‐metastatic functions of small extracellular vesicles from breast cancer cells. Issue 1 (30th October 2020) - Tan, Zengqi; Cao, Lin; Wu, Yurong; Wang, Bowen; Song, Zhihui; Yang, Juhong; Cheng, Lanming; Yang, Xiaomin; Zhou, Xiaoman; Dai, Zhijun; Li, Xiang; Guan, Feng
Abstract: Small extracellular vesicles (sEVs) are enriched in glycoconjugates and display specific glycosignatures. Aberrant expression of surface glycoconjugates is closely correlated with cancer progression and metastasis. The essential functions of glycoconjugates in sEVs are poorly understood. In this study, we observed significantly reduced levels of bisecting GlcNAc in breast cancer. Introduction of bisecting GlcNAc into breast cancer cells altered the bisecting GlcNAc status on sEVs, and sEVs with diverse bisecting GlcNAc showed differing functions on recipient cells. Carcinogenesis and metastasis of recipient cells were enhanced by sEVs with low bisecting GlcNAc, and the pro‐metastatic functions of sEVs was diminished by high bisecting GlcNAc modification. We further identified vesicular integrin β1 as a target protein bearing bisecting GlcNAc. Metastasis of recipient cells was strongly suppressed by high bisecting GlcNAc levels on vesicular β1. Our findings demonstrate the important roles of glycoconjugates on sEVs. Modification of sEV glycosylation may contribute to development of novel targets in breast cancer therapy.